2007
DOI: 10.1016/j.taap.2007.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution particles diminish bacterial clearance in the primed lungs of mice

Abstract: Epidemiological studies reveal increased incidence of lung infection when air pollution particle levels are increased. We postulate that one risk factor for bacterial pneumonia, prior viral infection, can prime the lung for greater deleterious effects of particles via the interferon-gamma (IFN-gamma) characteristic of successful host anti-viral responses. To test this postulate, we developed a mouse model in which mice were treated with gamma-interferon aerosol, followed by exposure to concentrated ambient par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 40 publications
(36 reference statements)
1
68
1
Order By: Relevance
“…27 Therefore, exposure to air pollutants, either through inhalation or ingestion, may induce inflammatory responses that are also evident in appendicitis. Alternatively, exposure to diesel exhaust has been shown to increase susceptibility to bacterial 28 and viral 29 pulmonary infections through impairment of microbial defence. 30 If air pollution similarly affects gastrointestinal immunity, exposure to pollutants may increase the risk of bacterial invasion resulting in appendicitis.…”
Section: Odds Ratio (95% Ci)mentioning
confidence: 99%
“…27 Therefore, exposure to air pollutants, either through inhalation or ingestion, may induce inflammatory responses that are also evident in appendicitis. Alternatively, exposure to diesel exhaust has been shown to increase susceptibility to bacterial 28 and viral 29 pulmonary infections through impairment of microbial defence. 30 If air pollution similarly affects gastrointestinal immunity, exposure to pollutants may increase the risk of bacterial invasion resulting in appendicitis.…”
Section: Odds Ratio (95% Ci)mentioning
confidence: 99%
“…There are reports, however, of increased numbers of hospitalizations for respiratory disorders including infections on days of increased levels of PM (2). In support of these epidemiologic findings, several rodent models have shown PM exposure can increase susceptibility to infectious bacteria such as Listeria monocytogenes and Streptococcus pneumoniae (3,4).…”
mentioning
confidence: 93%
“…It has also been demonstrated that nanoparticles can evade physical clearance mechanisms in humans, and enter or diffuse through cell membranes, leading to increased biodistribution and longer persistence in the body. In addition, it has been suggested repeatedly that the nanoparticle component of air pollution, such as particulate matter (PM 10 ), could be responsible for the increased susceptibility of individuals to respiratory infections in areas of high concentrations of air pollution by impacting the host response to the infection (3,4). However, no firm mechanistic understanding of this link has yet been demonstrated.…”
mentioning
confidence: 99%